2019
DOI: 10.3177/jnsv.65.192
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Dietary Polyphenol Intake and Its Seasonal Variations among Japanese University Students

Abstract: The intake of polyphenols among Japanese has been estimated in several adult populations, but there has been no information regarding their intake among young adults, especially in those in their twenties. We conducted a food frequency questionnaire (FFQ)based dietary assessment four times a year (once in each season) among Japanese university students and evaluated the total polyphenol intake across and within seasons. Forty-nine subjects (aged 20.760.6 y) completed our FFQ regarding polyphenol intake in Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
1
9
1
Order By: Relevance
“…In our evaluation, fruit and fruit juices, vegetable and extra virgin olive oil represent the main food categories providing polyphenols. In addition, we could not demonstrate a different selection of polyphenol sources depending on gender, despite some studies having reported a higher contribution from fruit and vegetables in females compared to males [8,34]. It is noteworthy that in the nursing home, the intake of coffee and wine was strongly limited, if not denied, to limit risks associated with caffeine and alcohol consumption and this may represent an important behavioural difference with respect to what may be observed in free-living older subjects.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In our evaluation, fruit and fruit juices, vegetable and extra virgin olive oil represent the main food categories providing polyphenols. In addition, we could not demonstrate a different selection of polyphenol sources depending on gender, despite some studies having reported a higher contribution from fruit and vegetables in females compared to males [8,34]. It is noteworthy that in the nursing home, the intake of coffee and wine was strongly limited, if not denied, to limit risks associated with caffeine and alcohol consumption and this may represent an important behavioural difference with respect to what may be observed in free-living older subjects.…”
Section: Discussioncontrasting
confidence: 82%
“…A major focus in this study was polyphenols because these compounds have the potential to provide further specific benefits to the target population under study. It has been reported that there is a large variation in the polyphenol content of foods available in different periods of the year [34][35][36], and for this reason we specifically analysed recipes and ingredients used to develop seasonal menus and the results obtained showed a relatively comparable amount of these bioactive compounds (about 770 mg per day on average as TPC) among the different seasons. We could not find other data on the impact of seasonality on polyphenol content of dietary plans provided in long-term residences for older people, while more literature is available in free-living older subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study was conducted from February to March. Several previous studies have reported seasonal differences in intakes among Japanese adults [ 55 58 ]. Thus, this limited period for the survey might have produced some bias in assessing the usual intake.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the SF-FFQ can easily calculate the total polyphenol intake by adding the points applied to each grade of frequency of intake of the listed items. The SF-FFQ yields information about only 12 foods and beverages items that have been shown to be important sources of total polyphenol intake in our previous studies (6)(7)(8)(9)(10)(11)(12). We have reported that the top 10 food and beverage items accounted for Ͼ80% of the total polyphenol intake, and the top 20 items accounted for Ͼ90%, indicating that a limited variety of items could contribute to the dietary polyphenol intake by Japanese (9).…”
Section: Resultsmentioning
confidence: 83%
“…It is somewhat burdensome for general populations to complete dietary record (DR) precisely and consistently, but FFQs are easy to answer and are useful for assessing long-term dietary habits. We have developed an original polyphenol content database, and we estimated the total polyphenol intake in several Japanese populations (6)(7)(8)(9)(10)(11)(12)(13)(14). We have also developed an original FFQ for polyphenol intake (9,12) that assesses the consumption frequency of 89 selected foods and beverages and requires approx.…”
mentioning
confidence: 99%